2010
DOI: 10.1002/cncy.20061
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of p16INK4A, Ki‐67, and human papillomavirus L1 capsid protein immunochemical staining on cell blocks from residual liquid‐based gynecologic cytology specimens

Abstract: BACKGROUND: This study was conducted to evaluate the reliability and role of cell block preparations in the diagnosis of neoplastic and preneoplastic lesions of the cervix and to improve the value of cell block preparations in diagnosing and predicting the prognosis of cervical lesions through immunostaining of p16INK4A (p16), Ki-67, and human papillomavirus (HPV) L1 capsid protein (HPV L1). METHODS: In total, 138 specimens were diagnosed on liquid-based cytology (LBC) and cell block preparations, and 63 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
1
41
0
1
Order By: Relevance
“…21,22 However, it is still hard to distinguish between a latent HPV infection with the potential of self-limitation and a transforming infection leading to the development of cervical neoplasia. 23 Therefore, recent studies proposed simultaneous immunocytochemical detection of p16 INK4a as a biomarker associated with high-risk HPV infection and Ki67 as a marker of a high cell proliferation rate, 24 …”
Section: Introductionmentioning
confidence: 99%
“…21,22 However, it is still hard to distinguish between a latent HPV infection with the potential of self-limitation and a transforming infection leading to the development of cervical neoplasia. 23 Therefore, recent studies proposed simultaneous immunocytochemical detection of p16 INK4a as a biomarker associated with high-risk HPV infection and Ki67 as a marker of a high cell proliferation rate, 24 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in histology only 2% of normal biopsies and 38% of CIN I showed diffuse staining for p16INK4a compared to 68% of CIN II and 82% of CIN III (Tsoumpou et al, 2009). In addition, the immunointensity and cells that were positive for p16 were enhanced according to increased pathologic grade and differed statistically between CIN-I and CIN-II/CIN-III as well as SCC (Yu et al, 2010). Our results revealed the p16 expression increased with the increase of the grade of cervical lesions.…”
Section: Clinical Significance Of P16 In the Cervical Intraepithelialmentioning
confidence: 53%
“…Compared with p16 alone, the combination with L1 may be particularly useful in assessing those lesions that are still in the productive phase of carcinogenesis. Yu et al (2010) also noted HPVL1/p16 expression patterns were related to the severity of cervical lesions. Yoshida et al (2008) performed liquid-based cytology in 63 patients and found that the detection rate of P16(-)/L1(+) in LSIL, HSIL and SCC was 44, 0 and 0%, respectively, and that of P16(+)/L1(-) was 82, 88 and 100%, respectively.…”
Section: Role Of Detection Of P16 and Hpvl1 Expressions In The Diagnomentioning
confidence: 73%
See 1 more Smart Citation
“…p16 in conjunction with Ki-67 provide high sensitivity for the detection of CIN2+ lesions (Schmidt et al, 2011;Yu et al, 2010).…”
Section: Applications In Cytologymentioning
confidence: 99%